The Impact of Decentralization on the Development of Football Cities in Türkiye: An Analysis of the Role of Local Governments in Sports Diplomacy - Zhein Nirwan Tawil (Institut Pemerintahan Dalam Negeri, 2026)
Abstract This study explores the impact of decentralization on the development of football cities in Türkiye, with a primary focus on the city of Trabzon. Football in Türkiye is not merely a sport but also a unifying social instrument that plays a significant role in the cultural identity of society. With decentralization, local governments have greater autonomy in managing the development of sports infrastructure, supporting talent development, and increasing public participation. This policy has encouraged the construction of sports facilities that strengthen local football communities and enhance the city's appeal both nationally and internationally. Furthermore, local governments leverage sports diplomacy to bolster the city's reputation on the global stage through hosting international events and collaborating with overseas clubs. This study analyzes decentralization policies that support football development in Trabzon and their impact on the socio-economic aspects of the local community. The findings indicate that decentralization significantly influences the development of Trabzon as a football city as it grants local authorities the fiscal and administrative autonomy to mobilize resources for sport infrastructure and implement structural athletic programs. Keywords: Football City, Decentralizaton, Local Governments Abstrak Studi ini mengkaji dampak desentralisasi terhadap pengembangan kota sepak bola di Türkiye, dengan fokus utama pada kota Trabzon. Sepak bola di Türkiye bukan sekadar olahraga, melainkan instrumen sosial yang memainkan peran penting dalam identitas budaya masyarakat. Dengan adanya desentralisasi, pemerintah daerah memiliki otonomi yang lebih besar dalam mengelola pembangunan infrastruktur olahraga, mendukung pengembangan bakat, dan meningkatkan partisipasi masyarakat. Kebijakan ini mendorong pembangunan fasilitas olahraga yang memperkuat komunitas sepak bola lokal serta meningkatkan daya tarik kota tersebut, baik di tingkat nasional maupun internasional. Selain itu, pemerintah daerah memanfaatkan diplomasi olahraga untuk memperkuat reputasi kota di kancah global melalui penyelenggaraan acara-acara internasional dan kerja sama dengan klub-klub luar negeri. Studi ini menganalisis kebijakan desentralisasi yang mendukung pengembangan sepak bola di Trabzon serta dampaknya terhadap aspek sosial-ekonomi masyarakat setempat. Temuan studi menunjukkan bahwa desentralisasi berpengaruh signifikan terhadap pengembangan Trabzon sebagai kota sepak bola, karena memberikan otonomi fiskal dan administratif kepada pemerintah daerah untuk memobilisasi sumber daya bagi infrastruktur olahraga serta melaksanakan program pembinaan atlet yang terstruktur. Kata kunci: Kota Sepak Bola, Desentralisasi, Pemerintah Daerah